PEMBELAJARAN MATEMATIKA BERBASIS ETNOMATIKA SEBAGAI SARANA PENANAMAN NILAI-NILAI KARAKTER PADA SISWA SEKOLAH DASAR - Ahmadizenad, Rafly; Zahra, Fatimah Az; Situmeang, Elmaria; Sagala, Paskah Valerius; Tarigan, Sry Nurliani Br; Naibaho, Regina Yolanda; Saragih, Gloria Luisa (Universitas Negeri Medan, 2025)
This study aims to analyze the implementation of ethnomathematics-based mathematics learning in instilling character values in elementary school students. This research uses a qualitative method with a literature study approach. The data collected are secondary, and are obtained from sources within a period of 10 years with a focus on literature that discusses the local wisdom of Indonesian culture and is analyzed descriptive-qualitatively through the stages of reading, understanding, identifying, comparing and compiling a synthesis of various literatures. compare, and compile synthesis from various literature The results of the study show that ethnomathematics-based mathematics learning is effective in instilling character values such as tolerance, local wisdom, creativity, cooperation, and honesty. Students are more motivated and enthusiastic about learning maths because learning is associated with the local culture they are familiar with. So that students who are academically intelligent, have character, creativity and cultural identity are formed. Ethnomatics-based mathematics learning has the potential to form students with strong character, creativity and cultural identity.